Arab Thought and People’s Movements as Event: Towards New Affective Registers of Critique - Sabry, Tarik (Javnost-The Public, 2018)
Historical events create the conditions under which thought processes develop in ways that make them symbolic of a whole generational shift, where a new cultural temporality comes to the fore both as un-concealment and as strategy. Significant shifts in the production of knowledge often suggest an epistemic and temporal break with the past where the relationship between event and theory is moved not merely by the new forms of knowledge it creates, but also by the new cultural temporality that these forms of knowledge bring to the fore as a strategy. In this article, I rehearse questions of an epistemological nature that grapple with the relationship between the people’s movements in the Arab region, as ethical events, and how these may have played a role in shifting the focus of Arab philosophical debate concerning questions of time, history and the body. Here, I rehearse the following questions: What kind of a thought/event conjecture are we dealing with in the case of the Arab/North African region? What is the connection between the movements as events, and the emerging Arab intellectual subject? And finally, what have the movements taught us about the relationships between thought, theory and the everyday?